High performance cementitious compounds and their application as transition substrate for beams - Ferrari, V. J.; Arquez, A. P.; De Hanai, J. B. (Revista ALCONPAT, 2016)
This study presents the development and analysis of the behavior of high performance cementitious compounds reinforced with fibers. The material described was specifically developed for its application as a transition substrate, meaning, a repair layer that forms the tensed span of the flexion reinforced concrete beams with carbon fiber reinforced polymers (CFRP). Nineteen different compounds were produced by the hybridization process. The volume of the short fibers and of the steel microfibers varied. To analyze the behavior of the flexural material, tests were done in three points in tests tubes with their notches. The response of the material was analyzed considering the tenacity parameters (to flexion and fracture). The high performance of the compounds through the behavior of pseudo-hardening was confirmed. Keywords: cementitious compounds; concrete beams; transition substrate.